Neonatal screening for biotinidase deficiency - Pinto, Anna L. R. (1998)
INTRODUCTION: Biotinidase deficiency is an inheritable disorder of biotin metabolism. This disorder fulfills major criteria for consideration for newborn screening: the affected children do not show clinical signs in the newborn period; the disease is highly disabling; treatment is effective in preventing neurological sequelae if undertaken promptly. MATERIAL AND METHODS: Screening of 125,000 infants born in Paraná State was carried out to establish the prevalence of biotinidase deficiency. A simple colorimetric procedure was used to detect two infants with biotinidase deficiency (1:62,500), one of them with profound deficiency (1:125,000) and the other with partial deficiency (1:125,000) of the enzyme. RESULTS: There were no known false-negative test results and 0.12% were false-positive, defined by further blood samples which were negative upon repeated testing. Sensitivity was 100% and specificity was 99.88%. Repeat blood samples could not be obtained in 63 (30%) suspected cases. CONCLUSIONS: Newborn screening for biotinidase is useful in identifying affected children, is inexpensive and allows early intervention, which may prevent irreversible neurological damage.